2007
DOI: 10.1080/00218460701282539
|View full text |Cite
|
Sign up to set email alerts
|

Peel-Zone Model of Tape Peeling Based on the Gecko Adhesive System

Abstract: A tape peeling model based on the geometry of the peel zone (PZ) is derived to predict the peeling behavior of adhesive tapes at peel angles less than or equal to 90o . The PZ model adds an angle-dependent multiplier to the 'Kendall equation' that takes into account the geometrical changes within the peel zone. The model is compared to experimental measurements of the peel force at different angles for a model tape and two commercial tapes, each with different bending moduli, stretch moduli and adhesive streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
169
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 167 publications
(180 citation statements)
references
References 37 publications
10
169
0
Order By: Relevance
“…This directional or anisotropic adhesive behaviour that allows smart or controllable surface attachment and detachment has inspired many applications such as climbing robots [7], clean transportation systems [8,9] and micro-transfer printing mechanisms [10]. Rapid switching of the gecko's toe pads between attachment and detachment can be attributed to millions of inclined seta shafts and to the corresponding loading response of the toes of the gecko [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This directional or anisotropic adhesive behaviour that allows smart or controllable surface attachment and detachment has inspired many applications such as climbing robots [7], clean transportation systems [8,9] and micro-transfer printing mechanisms [10]. Rapid switching of the gecko's toe pads between attachment and detachment can be attributed to millions of inclined seta shafts and to the corresponding loading response of the toes of the gecko [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The apparent peel-zone can be observed intuitively in experiments, and has been discussed and analysed in several articles [17,30,32,36,45]. The shape of the apparent peel-zone can be calculated by the earliermentioned numerical method and is approximately equivalent to a circular shape as shown in figure 11c, which in accordance with the microscopic observation reported by Pesika et al [17]. However, it is difficult to observe the compression region of peel region, as there is only a slight deformation [46].…”
Section: Appendix B Discussion On the Numerical Methodsmentioning
confidence: 99%
“…The peel angle, the length and shape of the peel region of the adhesive tape can significantly influence its mechanical peeling properties [6,17,[30][31][32]. It is practicable to fabricate adhesive surfaces with specially designed micro-fibrillar structures to modulate their reversible peeling and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Their model can explain why the gecko needs up to 1000 spatulae at the setal termination, but it did not consider the friction effect. Tian et al [23], Chen et al [24] and Pesika et al [25] used the peel-zone model to analyse the influence of the peeling angle on the adhesive force. They suggested that the peeling angle of the spatula can be adjusted by the digital gripping (DG) and digital hyperextension (DH) of the gecko.…”
Section: Introductionmentioning
confidence: 99%